Lithium Bis(fluorosulfony)imide‐Lithium Hexafluorophosphate Binary‐Salt Electrolytes for Lithium‐Ion Batteries: Aluminum Corrosion Behaviors and Electrochemical Properties. Issue 7 (15th February 2018) - Xia, Lan; Jiang, Yabei; Pan, Yueyang; Li, Shiqi; Wang, Jason; He, Yiting; Xia, Yonggao; Liu, Zhaoping; Chen, George Z.
Abstract: Aluminum corrosion behaviors and electrochemical properties of Lithium bis(fluorosulfony)imide (LiFSI)‐lithium hexafluorophosphate (LiPF6 ) binary‐salt electrolytes containing mixtures of LiFSI and LiPF6 (with a total salt content of 1.2 mol L −1 ) with different molar ratios in EC/EMC (3:7, by vol.) solutions are systematically investigated. Our experimental results from cyclic voltammetry, scanning electron microscopy (SEM), chronoamperometry and the charge‐discharge measurements of Li/LiNi1/3 Co1/3 Mn1/3 O2 half‐cells demonstrate that the LiFSI‐LiPF6 binary‐salt electrolytes with the LiFSI concentrations lower than 0.3 mol L −1 exhibit not only passivating aluminum current collectors at 4.3 V vs. Li + /Li, but also improved cycling performance. Meanwhile, Artificial Graphite/LiNi1/3 Co1/3 Mn1/3 O2 (AG/NMC111) pouch cells made with theLiFSI(0.2) ‐LiPF6 (1.0) electrolyte with the LiFSI concentration of 0.2 mol L −1 display an excellent cycling stability with 93.9% capacity retention at 1 C rate after 360 cycles, and enhanced capacity retention at −20 °C, 60 °C and after 55 °C storage for 30 days compared to cells with 1.2 mol L −1 LiPF6 /EC‐EMC conventional electrolyte. This work confirms that binary‐salt electrolytes system, such as LiFSI‐LiPF6, may be a promising method to enhance the longevity and storage properties of Li‐ion batteries. Abstract : Aluminum corrosion behaviors and electrochemical properties of LiFSI‐LiPF6 binary‐salt electrolytes were systematically investigated. When the LiFSI concentration is lower than 0.3 mol L ‐1, the severe corrosion of the aluminium is effectively suppressed. AG/ LiNi1/3 Co1/3 Mn1/3 O2 pouch cells made with the LiFSI(0.2) ‐LiPF6 (1.0) binary‐salt electrolyte display an excellent cycling stability, and enhanced capacity retention at ‐20°C, 60°C and after 55°C storage for 30 days. This work confirms that the LiFSI‐LiPF6 binary‐salt electrolyte may be a promising in Li‐ion battery industry.